Modern approaches to the rehabilitation of people with chronic back pain of various genesis - Tereshchuk Ольга; Dorofieieva Олена; Yarymbash Ксенія (Psychosomatic Medicine and General Practice, 2024)
This text is the abstract of the report of the Scientific and Practical Conference "War Trauma. Multimodal Approach in Inpatient Treatment", June 22 - 22, 2024, online and offline - Kyiv, 21 Akademika Zabolotnoho St., Clinical Hospital "Feofania" of the State Medical University.